The Effect of Manganese on Chloroplast Structure and Photosynthetic Ability of Chlamydomonas reinhardi - Teichler-Zallen, Doris (1969)
Manganese deficiency was induced in mixotrophically-grown cultures of the green alga Chlamydomonas reinhardi and the effects of this deficiency on photosynthetic activity and cell structure were investigated. Manganese-deficient cells are unable to carry out, at normal rates, photosynthetic reactions involving system II of the photosynthetic electron transport chain. Reactions requiring only system I are not inhibited. Normal system II activity returns within 2 hr in the light following addition of manganous ions to deficient cells. Significant structural alterations for deficient cells were observed in the chloroplast, in the arrangement of discs into stacks. Stacking distributions for normal, deficient, and recovered cells were quantitatively characterized and compared by the introduction of an experimentally-defined distribution function and its attendant parameters. The results provide evidence for a role for manganese in maintaining chloroplast structure.